Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1600-6143.2012.04045.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Kidney Rejection After Combined Bone Marrow and Renal Transplantation Despite Ongoing Whole-Blood Chimerism in Rhesus Macaques

Abstract: Although there is evidence linking hematopoietic chimerism-induction and solid organ transplant tolerance, the mechanistic requirements for chimerism-induced tolerance are not clearly elucidated. To address this, we used an MHC-defined primate model to determine the impact of impermanent, T cell-poor, mixed-chimerism on renal allograft survival. We compared two cohorts: one receiving a bone marrow + renal transplant (“BMT/renal”) and one receiving only a renal transplant. Both cohorts received maintenance immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
21
1
Order By: Relevance
“…However chimerism eventually disappeared after dicontinuation of immunosuppression (30). In their subsequent study, they performed combined kidney and bone marrow transplantation using the same conditioning regimen (31). In contrast to our results, all five recipients rejected their kidney allografts despite successful chimerism induction.…”
Section: Discussionmentioning
confidence: 99%
“…However chimerism eventually disappeared after dicontinuation of immunosuppression (30). In their subsequent study, they performed combined kidney and bone marrow transplantation using the same conditioning regimen (31). In contrast to our results, all five recipients rejected their kidney allografts despite successful chimerism induction.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated the successful induction of long-lived (> 1 year) myeloid-predominant chimerism with this regimen. (1, 3538) However, unlike in mice, reduced-intensity busulfan-only conditioning in NHP did not lead to significant T cell chimerism (35, 36) and without significant T cell chimerism, the donor hematopoietic graft was eventually rejected by host T cells (35, 36, 39) (at a pace directly related to the degree of MHC disparity). (36) This transient chimerism did not induce tolerance to renal allografts.…”
Section: Introductionmentioning
confidence: 99%
“…A recent article in AJT by Ramakrishnan et al (1), referring to a recent report from our group (2), suggested that we had achieved tolerance of renal allografts in non-human primates via mixed chimerism only in highly MHC-matched transplant pairs. This interpretation of our experience is not fully accurate.…”
Section: To the Editormentioning
confidence: 95%